Frequency of Diplopia in Zygomatic Fractures - Atiq Ur Rahman, Maqbool Ur Rehman, Abdul Munem, Maria Saleem, Mansoor Ahmed, Karamat Ullah, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: A zygomatic fracture is a type of face fracture resulting from a break in the zygomatic bone. It is frequently the result of facial injuries caused by automobile accidents, physical assault, falls, etc, often associated with pre and post-operative ocular complications. Objectives: Therefore, this research was conducted to determine frequency of diplopia in zygomatic fractures. Methods: The study was executed from June 2020 to November 2022 on 241 patients admitted to the MMMT Hospital, Dera Ismail Khan and data pertaining to diplopia due to zygomatic fractures was recorded at the initial and final visits of the patients. The preoperative and postoperative adverse effects of diplopia were critically examined. Results: The frequency of diplopia in the zygomatic fractures of the study group was determined to be 38.58 percent, with 93 individuals affected. It was also seen that 52 individuals out of 132 were affected with diplopia in road accidents, followed by 16 in physical assaults, 9 in fall injury, 9 in the workplace, and 7 individuals were injured while playing sports, with the respective frequencies being 39.39, 35.55, 42.85, 42.85, and 25.92%. Conclusion: It was concluded from the study that zygomatic fractures continued to be one of the most prevalent maxillofacial fractures and were commonly caused by road accidents. The highest occurrence was observed in young male patients and was frequently linked to ocular problems and the incidence of diplopia was significant among patients with zygomatic fractures (38.58%). In order to limit the frequency of diplopia in cases of zygomatic fractures, it was recommended that surgical treatment of zygomatic fractures be performed promptly to prevent ocular complications. Keywords: Diplopia; Mandibular fractures; Ocular complications; Road accidents; Zygomatic fractures.